Combination dual therapy of Empagliflozin and Linagliptin for the management of Type 2 Diabetes - Arun Daniel; Atanu Kundu; Balamurugan; Bhabani Bhuyan; Chaitanya Challa (Medico Research Chronicles, 2020)
Patients with type 2 diabetes (T2DM) have a significantly higher risk of developing cardiovascular disease (CVD) - namely myocardial infarction, heart failure and stroke 1. Despite the efforts and advancements, the impact of T2DM on CVD outcomes remains high and continues to escalate. With the escalation in the severity of hyperglycemia, macrovascular complications increases, thus suggesting an almost linear relation between metabolic disturbances and vascular damage